A Case of Hemothorax as Manifestation of Thoracic Endometrial Syndrome - Sandra Patrucco Reyes MD; Kwesi Amoah MD; Mandeep Singh Rahi MD; Kulothungan Gunasekaran MD (Journal of Investigative Medicine High Impact Case Reports, 2021)
Thoracic endometriosis is a rare progression of a mostly benign disease of ectopic endometrial activity involving the pleura and lung. This is a case of a young female who presented with progressive shortness of breath and was found to have significant anemia. Further investigations showed a massive right-sided pleural effusion and ascites. Subsequent thoracentesis and pelvic diagnostic laparoscopy showed a hemorrhagic pleural effusion and ascites, along with dense pelvic adhesions. Pathology was consistent with endometriosis. Patient improved on leuprolide acetate and norethindrone. This case illustrates an important consideration in the differential of a reproductive-age female with new onset shortness of breath and anemia.